Mainstreaming the Values of Religious Moderation in a Multicultural Environment in Islamic Religious College in East Kalimantan - Akhmad Muadin; Mukhamad Ilyasin (SYAMIL: Journal of Islamic Education, 2024)
The mainstreaming policy of religious moderation which is promoted throughout PTKI under the auspices of the Ministry of Religion, makes Sultan Aji Muhammad Idris Samarinda State Islamic University one of the institutions that take part in implementing the policy in order to equate the values of religious moderation. In this case, the institution seeks to internalize the values of religious moderation in the hope that these values can become part of identity that can be practiced in everyday life. The purpose of the study is to describe the results of research that focuses on how the process of internalizing the values of religious moderation and its implications for social attitudes from the implementation of the internalization. The research method used is descriptive qualitative. Data collection techniques in the form of observation, interviews, and documentation. The data analysis technique uses the Miles, Huberman and Saldana model, namely data condensation, data presentation, and drawing conclusions. The data validity technique uses source triangulation and technical triangulation. The results of this study indicate that in internalizing the values of religious moderation at the State Islamic University of Sultan Aji Muhammad Idris Samarinda, several efforts were made to support this, including curriculum policies by presenting Islamic & Religious Moderation courses, research recommendations with the theme of religious moderation, community service as well as several activities whose content contains the values of religious moderation in them.